Diagnosis of Tropical Cyclone Structure and Intensity Change - Keyser, Daniel (1998)
Objectives: a. To investigate the origin and evolution of tropopause-based precursor disturbances that culminate in rapid maritime cyclogenesis over the western North Atlantic Ocean. b. To investigate the roles of trough interactions in tropical-cyclone intensity change with a view toward determining the factors that distinguish between cyclogenetic and cyclolytic trough interactions. c. To investigate the roles of environmental dynamical effects on tropical-cyclone structure and intensity change. d. To investigate the kinematics of vorticity asymmetries associated with nondivergent barotropic vortices on a beta-plane. See also ADM002252.